Ethical Perception for Journalistic Profession. Academic Reality vs. Occupational Reality - Hormazábal, Constanza (2017)
The report “Journalism’ students in Chile: Perception of the profession, their future work field and the performance of the media” (Mellado & cols., 2015), which includes their perspective about career field, evaluation and use of the media, threats and future of journalism, and ethics, among others, is the starting point of an exploratory investigation to account the ethical perception of journalism students, against controversial practices and their relation to join the labor market. Based on the analysis, getting deeper in the findings of this report and the contrast with the curricula of the participating journalism schools, the students’ vision is extrapolated from the reality observed in their first professional experience, based on the perception of the media editors. In this way, this report tries to determine how the student’s ethical perception is put to the test in his first professional experience.